Knowledge, innovation, and outcomes in craft beer: theoretical framework and fuzzy-set qualitative comparative analysis - Cabrera-Flores, Mayer Rainiero (My University, 2020)
This paper explores the relationship between knowledge, innovation, and profit-making in the craft beer industry in Baja California, Mexico. The research highlights the cultural nature of this industry, in which the depth of culture and tradition bolster the capacity for innovation. One source of interest in the study of cultural industries is the importance of businesses in regional development, as is happening in the Baja California region with craft beer. At its core, this study draws on the SECI model as a reference to highlight the different ways in which knowledge and learning combine to produce new forms of processes or products or break into new market segments. This empirical study is based on the fuzzy-set qualitative comparative analysis method (FsQCA), which serves to identify sequences or combinations of knowledge and learning that lead to innovation and profit.
Journal of Intelligent & Fuzzy Systems
Keywords: Craft beer industry; Tacit knowledge; Campus Ensenada